Penerjemahan Kata Demi Kata Pada Komposisi Minuman Seduh - Muhamad Muzaky Ramdhan (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2023)
This research entitled is “Penerjemahan Kata demi Kata pada Komposisi Minuman Seduh”. The purpose of this study are to explain the translation used in the composition text for brewed drinks. This study used descriptive qualitative method. The data collection techniques that used in this research is literature study. The data used are primary from 10 brewed drinks composition texts (Tora Bika Gilus Mix, ABC Kopi Susu, Tora Bika Mocacinno, Indocaffe CafeMix, Goodday Carrebian Nut, Goodday Mocacinno, Kapal Api, Top White Coffee, Top Cofee, Top Barista Spcial Blend). Data analysis was carried out by reading and understanding from brewed beverage packaging, presenting the data to be analyzed for this reserch and making conclusions. The results of this study is answering that the translation used in the compositions tesxt of brewed drinks is word for word translation, namly by direcly translation the source language to target language in a straight line between lines.